An Investigation into the Regenring Act in an ESP Reading and Writing Course - Elaheh Suleimani (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2021)
Focusing on instruction of schematic structures and generic models are the primary characteristics of traditional genre pedagogy. What demands to be explored is how a particular knowledge structure could be reconfigured into a new genre. As a result, in this paper the effect of regenring in an ESP reading and writing course was investigated. For this purpose, two hundred and forty regenred annotations of writing were collected from twenty EFL participants in an ESP reading and writing course. It was found that regenring brought about genre awareness and changed the participants’attitudes toward their disciplinary topics and fields of study. Consequently, it may be assumed that regenring will contribute to awareness of how reconfiguration of knowledge in a new genre illuminates affordances and possibilities of a fresh experience and a new outlook on the subject matter. Due to its great potentiality, it is recommended to use regenring technique in writing pedagogy.